Implementasi Konsep Good Samaritan Law Sebagai Alternatif Perlindungan Tenaga Medis dan Tenaga Kesehatan dalam Pelayanan Kegawatdaruratan - Inna Noor Inayati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Medical emergency services demand swift and precise action; however, medical personnel are often hindered by the risk of criminalization resulting from unintended outcomes. Although Law Number 17 of 2023 concerning Health mandates the provision of assistance, the regulation has not yet provided explicit criminal protection for good-faith rescuers, thereby triggering the practice of defensive medicine. This study aims to examine the implementation of the Good Samaritan Law (GSL) concept as an alternative legal protection for health workers. The research methods employed are juridical-normative and juridical-empirical, utilizing statutory, comparative, and case approaches. The findings indicate that current regulations, including Article 531 of the Criminal Code (KUHP) and Law No. 17/2023, have limitations as they emphasize the obligation to assist rather than the protection of the rescuer. In comparison, the international GSL concept offers a standard of